Respuesta :
1st -- multiplying the left side = 3c+12 which equals to 2c+9 then subtracting 2c from both sides which equal to the c=-3. Answer is -3.
If you would like to solve the equation 3/4 * (4 * c + 16) = 2 * c + 9, you can calculate this using the following steps:
3/4 * (4 * c + 16) = 2 * c + 9
3/4 * 4 * c + 3/4 * 16 = 2 * c + 9
3 * c + 12 = 2 * c + 9
3 * c - 2 * c = 9 - 12
c = - 3
The correct result would be - 3.
3/4 * (4 * c + 16) = 2 * c + 9
3/4 * 4 * c + 3/4 * 16 = 2 * c + 9
3 * c + 12 = 2 * c + 9
3 * c - 2 * c = 9 - 12
c = - 3
The correct result would be - 3.